O uso de recursos tecnológicos no processo de alfabetização na relação grafema-fonema - Pastre, Patrícia Fernanda Morés (2024)
This research was carried out in the Postgraduate Program in Education (PPGEdu), Educational Processes and Language research line, at the University of Passo Fundo, Rio Grande do Sul. The study deals with the grapheme-phoneme relationship in children in the early childhood phase. literacy with the use of digital technologies. The legislation provides that children's literacy will be completed up to the 2nd year of elementary school. In this sense, after changes in legislation, a post-pandemic period and the intense use of Digital Communication and Information Technologies (DICT) by children, there is a historical concern about the effectiveness of teaching methodologies. This scenario refers to the research problem: How can the use of Digital Information and Communication Technologies (DICT) contribute to the literacy process with regard to the grapheme-phoneme relationship? The general objective is to explore ways of enhancing the grapheme-phoneme relationship in children in the literacy phase using digital technologies. The specific objectives refer to describing the cognitive learning processes that occur during the literacy phase and identifying technologies that can be used in the literacy process in view of the grapheme-phoneme relationship. To this end, theoretical research was based on the assumptions of the National Curricular Guidelines for Basic Education (DCNs, 2013), the National Common Curricular Base (BNCC, 2018), the Base Curriculum for Early Childhood Education and Elementary Education in the Catarinense Territory (CBTC , 2019), as well as in the Literacy Policy for the Santa Catarina State Education Network (2021). The study of these documents and the framework based on the writings of Soares (2017), Morais (2012; 2022) and Lerner (2002) guided the organization of the intervention research (Damiani, 2012), of a qualitative nature, and the analysis of the data ( Bardin, 2011). The different proposals for activities developed using Digital Communication and Information Technologies (TDIC) occurred with students in the 2nd year of Elementary School. It was evident that the grapheme-phoneme relationship permeates the planning of activities, with pedagogical intentionality and different teaching methodologies, in addition to criteria defined according to the skills desired for literacy. It is concluded that the use of TDIC enhances the grapheme-phoneme relationship and contributes significantly to the literacy process.